Proliferasi dalam Era Desentralisasi Fiskal Menuju Pertumbuhan Ekonomi, Pembangunan Daerah dan Pengentasan Kemiskinan - Temenggung, Yuswandi Arsyad; Moenek, Reydonnyzar; Suwanda, Dadang; Mulyadi, Mohammad (Jurnal Bina Praja, 2020)
Indonesia has conducted territorial expansion to improve public services, create more effective governance, and increase regional development. Territorial expansion was accompanied by fiscal Decentralization, so that allowed the regions to manage their finances by arranging regional development programs and other planning. However, in its implementation, Decentralization, which has been running for two decades, has experienced problems such as the financial over-dependence on central government and development inequity, which has further implications for eradicating the poor. The purpose of this research is to analyze to what extent the territorial expansion that have been running is able to increase the fiscal revenue of new autonomous regions (DOB) in order to maximize economic growth, equitable territorial development and regional development to be able to eradicate the poor and improve the welfare of the community. The research method uses descriptive methods with a qualitative approach. This study uses data from a period of 2015 to 2019 in accordance with the National Mid-Term Development Plan (RPJMN). The results showed that the development of new autonomous regions in the era of post-reform regional autonomy were 8 provinces, 181 districts and 34 cities. Therefore, the allocation of transfer funds to the regions is increasing every year. For the 2020 State Budget, around Rp.858 trillion or around 34.6% of total state expenditure. However, ironically, the over-dependence of DOB on fiscal Decentralization has not declined. If seen from the ratio of PAD to total regional income, it is known that DOB currently still depends on the parent region or central government, while the DOB growth rate is lower comparing to their parent region. On the other hand, the focus of DOB development is more on government facilities and infrastructure. Although in some new autonomous regions, there is a decrease in poverty, in general, poverty levels in new autonomous regions are relatively higher than in parent regions.